Biochar Carbon Sequestration in Soil - A myth or Reality? - Purakayastha, T. J.; Kumari, Savita; Sasmal, Subodh; Pathak, H. (International Journal of Bio-resource and Stress Management, 2023)
The soil carbon sequestration is the long-term storage of carbon in soil which could well be accomplished by the application of biochar as a soil amendment. Biochar (BC) is a fine grained, highly carbonaceous, pyrolysed (low temperature) product of biomass. The pyrolysis temperature strongly influences the stability of biochar in soil; the higher the pyrolysis temperature higher would be the stability. Biochar being highly stable in soil due to its aromaticity, presence of amorphous structure and turbostatic crystallites, rounded structures and reduced accessibility to decomposers has lot of potential for long-term carbon sequestration. The higher stability of biochar in soil is also due to strong interactions with mineral surfaces. Biochar interacts with native soil organic matter (SOM) in a complex way; sometimes biochar showed positive priming effect or negative priming effect or no effect on native SOM. This depends upon the feedstock type, pyrolysis temperature and organic matter level of soil. The soils richer in organic matter status provide positive priming effect of native SOM due to biochar addition and vice-versa. Biochar has high carbon sequestration potential and long-term influence on native SOM. Biochar has huge potential for reduction of greenhouse gas emission form paddy field soils. Therefore, optimisation of feedstock, pyrolysis temperature for preparation biochar and its application in a specific soil is extremely essential for stability of biochar and protection of native SOM and greenhouse gas reduction for long-term carbon sequestration. Thus biochar carbon sequestration is not a myth rather it would be a reality in near future.